2004
DOI: 10.2175/193864704784107515
|View full text |Cite
|
Sign up to set email alerts
|

Development of Milwaukee Msd's Private Property Infiltration and Inflow Control Program

Abstract: The MMSD has been investigating control of private infiltration and inflow (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The United States Environmental Protection Agency (2000) mentions that even when pipe materials are more resistant to acids and chemicals, the joints are not. Even though literature indicates that lateral house connections cover 21-47% of the total length of the entire sewer system (Gonwa et al, 2004;Princ & Kohout, 2004), these components contribute 30-55% of the total infiltration (Curtis & Krutsch, 1993;Ellis, 2001;Sullivan et al, 1977;Water Environment Federation, 1999). Several authors reported that the connection with the main sewer is the weakest point (Ellis et al, 2004;Princ & Kohout, 2004).…”
Section: Pipe Collapsementioning
confidence: 99%
“…The United States Environmental Protection Agency (2000) mentions that even when pipe materials are more resistant to acids and chemicals, the joints are not. Even though literature indicates that lateral house connections cover 21-47% of the total length of the entire sewer system (Gonwa et al, 2004;Princ & Kohout, 2004), these components contribute 30-55% of the total infiltration (Curtis & Krutsch, 1993;Ellis, 2001;Sullivan et al, 1977;Water Environment Federation, 1999). Several authors reported that the connection with the main sewer is the weakest point (Ellis et al, 2004;Princ & Kohout, 2004).…”
Section: Pipe Collapsementioning
confidence: 99%